Clinical Image of Darwin’s Tubercle: A Rare Auricular Variant - Parindita Sarmah; Prasad Deshmukh; Sagar Gaurkar (Journal of Clinical and Diagnostic Research)
A 13-year-old male presented to the Ear, Nose and Throat (ENT) Department complaining of a “bump” on the upper part of his left ear. The patient had noticed this prominence since childhood but reported no associated pain or discomfort. His primary concern was cosmetic, seeking reassurance and information about the condition. On physical examination, a cartilaginous prominence approximately 5 mm in diameter was noted on the posterosuperior aspect of the helix of the left pinna [Table/Fig-1]. The overlying skin was unremarkable, and there was no tenderness, erythema, or discharge. The rest of the otoscopic examination was within normal limits.